2017
DOI: 10.1596/1813-9450-8187
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Digital Technologies on Routine Tasks: Do Labor Policies Matter?

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 20 publications
1
16
0
2
Order By: Relevance
“…Data of routine task intensity comes from the O*NET 2000 release, which associates the importance of certain tasks to 800 occupations in the United States. Following Almeida, Corseuil, and Poole (2017), and assuming that occupations in Brazil entail similar tasks as the U.S., occupations are assigned a routine intensity. These are matched with the Brazilian occupation system CBO 30 .…”
Section: Routine Task Intensitymentioning
confidence: 99%
“…Data of routine task intensity comes from the O*NET 2000 release, which associates the importance of certain tasks to 800 occupations in the United States. Following Almeida, Corseuil, and Poole (2017), and assuming that occupations in Brazil entail similar tasks as the U.S., occupations are assigned a routine intensity. These are matched with the Brazilian occupation system CBO 30 .…”
Section: Routine Task Intensitymentioning
confidence: 99%
“…Dachs (2018) also found that new technologies substituted for routine tasks and that a high share of tasks require creative and social skills. Moreover, Almeida et al (2017) also investigated the impact of digital technologies on worker tasks. They investigated about 16m workers in 2,312 occupations in Brazil.…”
Section: Technology Adoption and Labor Demandmentioning
confidence: 99%
“…In a similar study, show that the adoption of computers by households in Vietnam is strongly associated with increases in the demand for non-routine manual tasks and routine cognitive tasks. Based on employer-employee data from Brazil, Almeida et al (2017a) find that the rollout of the internet between 1996 and 2006 was associated with a reduction in employment and a fall in demand by technology-intensive industries for routine tasks, thus shifting the composition of employment towards non-routine tasks. Finally, Almeida et al (2019) find that the use of advanced software reduces the relative demand for analytical skills by Chilean firms.…”
Section: Literature Reviewmentioning
confidence: 99%